Astrocyte development in the cerebral cortex: Complexity of their origin, genesis, and maturation - Clavreul, Solène; Dumas, Laura; Loulier, Karine (Frontiers in Neuroscience, 2022)
In the mammalian brain, astrocytes form a heterogeneous population at the morphological, molecular, functional, intra-, and inter-region levels. In the past, a few types of astrocytes have been first described based on their morphology and, thereafter, according to limited key molecular markers. With the advent of bulk and single-cell transcriptomics, the diversity of astrocytes is now progressively deciphered and its extent better appreciated. However, the origin of this diversity remains unresolved, even though many recent studies unraveled the specificities of astroglial development at both population and individual cell levels, particularly in the cerebral cortex. Despite the lack of specific markers for each astrocyte subtype, a better understanding of the cellular and molecular events underlying cortical astrocyte diversity is nevertheless within our reach thanks to the development of intersectional lineage tracing, microdissection, spatial mapping, and single-cell transcriptomic tools. Here we present a brief overview describing recent findings on the genesis and maturation of astrocytes and their key regulators during cerebral cortex development. All these studies have considerably advanced our knowledge of cortical astrogliogenesis, which relies on a more complex mode of development than their neuronal counterparts, that undeniably impact astrocyte diversity in the cerebral cortex.